Survival and organ involvement in patients with limited cutaneous systemic sclerosis and anti-topoisomerase-I antibodies: determined by skin subtype or auto-antibody subtype? A long-term follow-up study. (12th August 2016) - Kranenburg, Pim; van den Hombergh, Wieneke M. T.; Knaapen-Hans, Hanneke K. A.; van den Hoogen, Frank H. J.; Fransen, Jaap; Vonk, Madelon C.
Abstract : Objective. LcSSc is associated with ACAs and a mild course, whereas dcSSc is associated with anti-topoisomerase antibodies (ATAs) and a more severe course. However, ATAs are also present in lcSSc. Little is known about survival and organ involvement in this subgroup. The aim of this study is to determine whether survival and organ involvement of lcSSc ATA-positive patients differs from lcSSc ATA-negative or dcSSc ATA-positive patients. Furthermore, transition from lcSSc to dcSSc was evaluated. Methods. Data from The Nijmegen Systemic Sclerosis cohort were used, with up to 15 years of follow-up. Kaplan–Meier analysis was performed for survival and organ involvement, including interstitial lung disease, pulmonary arterial hypertension, cardiac involvement and Scleroderma Renal Crises. Cox proportional hazard modelling was performed to adjust for confounders. Results. A total of 460 patients were included: 58 (13%) lcSSc ATA-positive patients, 237 (52%) lcSSc ATA-negative patients and 78 (17%) dcSSc ATA-positive patients. Cumulative survival in lcSSc ATA-positive patients was 75%, in lcSSc ATA-negative patients 58% and in dcSSc ATA-positive patients 53%. Interstitial lung disease was more prevalent in lcSSc ATA-positive patients (49%) than in lcSSc ATA-negative patients (25%), but less than in dcSSc ATA-positive patients (60%). Forty-eight patients developed dcSSc: 24 ATA-negative and 24 ATA-positive (P < 0.001). Conclusion. LcSSc ATA-positive patients differ from lcSSc ATA-negative patients and dcSSc ATA-positive patients concerning survival and organ involvement. LcSSc patients who are ATA-positive are more likely to develop dcSSc than lcSSc patients who are ATA negative.